2019
DOI: 10.1007/s13595-019-0904-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing site form as an indicator of site quality in even-aged Pinus radiata D. Don stands in north-western Spain

Abstract: & Key message Site form and site index have shown similar precision for estimating site quality in even-aged Pinus radiata D. Don stands in northwestern Spain. Additionally, SF presents the advantage that it does not require stand age information and can therefore be used in a wider set of situations in the forestry practice. & Context Estimation of site quality is essential for characterizing, monitoring and predicting forest resources. Site index (i.e. the dominant height of the stand at a reference age) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
6
0
5
Order By: Relevance
“…Likewise, Fu et al [ 12 ] used ADA to test the SF MH-MD in two natural uneven-aged forests of Larix Olgensis Henry and Quercus Mongolica Fisch in northeastern China, which showed correlation coefficients of 0.55 and 0.79. On the other hand, Molina-Valero et al [ 13 ] reported a correlation of 0.71 in Pinus radiata D. Don even-aged stands in the north of Spain using GADA to test the SF MH-MD . Therefore, the effectiveness of the SF may vary based on the model used and the type of forest evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Fu et al [ 12 ] used ADA to test the SF MH-MD in two natural uneven-aged forests of Larix Olgensis Henry and Quercus Mongolica Fisch in northeastern China, which showed correlation coefficients of 0.55 and 0.79. On the other hand, Molina-Valero et al [ 13 ] reported a correlation of 0.71 in Pinus radiata D. Don even-aged stands in the north of Spain using GADA to test the SF MH-MD . Therefore, the effectiveness of the SF may vary based on the model used and the type of forest evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the SF has also been called the site productivity index [ 11 ]. It has been successfully used as an indicator of productivity in uneven-aged stands [ 12 ] and has delivered meaningful results in even-aged forests [ 13 ]. Nonetheless, the main feature of SF is its capacity to describe site quality in uneven-aged multispecies forests [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site index measures stand productivity based on the height of dominant or co-dominant trees at a given reference age, usually 50 years, and is often expressed in feet or meters [24,25]. Dominant or co-dominant trees are used to assess site productivity because it is assumed that their height growth has not been impacted by stand density [26]. Site index is theorized to be a function of topographic variables, such as aspect and elevation, together with soil characteristics, such as soil type and fertility, and climatic variables, such as annual precipitation and maximum summer temperatures [27].…”
Section: Introductionmentioning
confidence: 99%
“…In any projection-based approach to predicting future yield, a quantitative understanding of site quality, or the inherent potential of a site to support forest growth, is an essential component of the modelling system. Molina-Valero et al (2019) tackled the problem by considering the potential of the lesser-used "Site Form" (SF) as compared to much more widely utilised estimates of "Site Index" (SI). They showed that the two methods gave comparable overall accuracy and, given that SF does not require information on stand age, further research considering this lesser-used approach seems worthwhile.…”
mentioning
confidence: 99%